2022
DOI: 10.1111/jocd.14743
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with oral vitamin D alone, topical minoxidil, or combination of both in patients with female pattern hair loss: A comparative clinical and dermoscopic study

Abstract: Background One of the most common dermatological complaints among female is female pattern hair loss (FPHL). Serum vitamin D is a factor lately taken into consideration in approaching patients complaining of hair loss. Aim To evaluate the serum level of 25‐hydroxy vitamin D in patients with FPHL and to evaluate the efficacy of vitamin D therapy alone or combined with minoxidil in the treatment of this disease. Methods 45 patients with FPHL and 15 controls to measure serum level of vitamin D were enrolled in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Data is scarce regarding the efficacy of vitamin D supplementation or topical solution for patients with vitamin D deficiency and concomitant alopecia. However, animal model studies have found benefit with vitamin D supplementation [69], and oral vitamin D supplementation with minoxidil was found to be significantly more effective than minoxidil alone in the treatment of FPAnA [70]. Yet, oral vitamin D monotherapy did not result in significant improvement.…”
Section: Vitamin Dmentioning
confidence: 98%
“…Data is scarce regarding the efficacy of vitamin D supplementation or topical solution for patients with vitamin D deficiency and concomitant alopecia. However, animal model studies have found benefit with vitamin D supplementation [69], and oral vitamin D supplementation with minoxidil was found to be significantly more effective than minoxidil alone in the treatment of FPAnA [70]. Yet, oral vitamin D monotherapy did not result in significant improvement.…”
Section: Vitamin Dmentioning
confidence: 98%
“…Research data showed a link between a poor serum vitamin D levels and telogen effluvium (28). Recent studies report that for female pattern baldness, the use of oral vitamin D together with topical minoxidil has better results than applying minoxidil alone (29). Biotin Although it has become popular among consumers, biotin has not been shown to be effective in healthy individuals for nail and hair growth.…”
Section: Supplementation and Treatment Strategies Multivitaminsmentioning
confidence: 99%